2017
DOI: 10.1080/17458080.2017.1285446
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of TiO2 nanofibre/cellulose acetate nanocomposite ultrafiltration membrane

Abstract: Nanofibres of TiO 2 were synthesised by hydrothermal routine. Cellulose acetate/TiO 2 nanofibre composite membranes were synthesised via blending TiO 2 nanofibre in cellulose acetate solutions in 1-methyl-2-pyrrolidone. In order to study the effect of addition of nanofibre, membranes with various composition were synthesised, first by keeping cellulose acetate to 1-methyl-2pyrrolidone ratio constant and second by decreasing cellulose acetate concentration with increasing addition of TiO 2 nanofibre. The membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, the missing roughness in microscale and nanoscale led to it showing water-superabsorbent states after UV illumination. Neelapala et al (2017) successfully incorporated TiO2 into cellulose acetate (CA) via phase inversion and then fabricated nanocomposite membranes. The addition of TiO2 resulted in a decrease in finger-like projection and formed spongy structure, so the hydrophilicity of the CA membrane and the antifouling property significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…However, the missing roughness in microscale and nanoscale led to it showing water-superabsorbent states after UV illumination. Neelapala et al (2017) successfully incorporated TiO2 into cellulose acetate (CA) via phase inversion and then fabricated nanocomposite membranes. The addition of TiO2 resulted in a decrease in finger-like projection and formed spongy structure, so the hydrophilicity of the CA membrane and the antifouling property significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been done by researchers to improve the hydrophilicity of cellulosic membranes, as shown in Table 1. Benavente et al [5], Pereira et al [6] and Neelapala et al [7] improved the hydrophilicity of membranes by using nanoparticles. The findings showed that the modified membranes exhibited excellent E-coli inhibition, high flux and low contact angle properties.…”
Section: Introductionmentioning
confidence: 99%